2003
DOI: 10.1021/jf034365p
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol and Fatty Acid Compositions of French Virgin Olive Oils. Characterization by Chemometrics

Abstract: There is no data concerning the fatty acid and triacylglycerol composition of French virgin olive oil. Thus, these compositions were determined using 564 samples coming from four olive harvests (1998-1999 to 2000-2001). Among these 564 samples, 372 came from the four main French cultivars (Aglandau, Cailletier, Picholine, and Salonenque) and from both of the oldest French protected designations of origin: "Nyons" (cv. Tanche) and "Vallée des Baux". The fatty acid compositions took the different isomeric monoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
138
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 9 publications
17
138
0
1
Order By: Relevance
“…The differences in squalene levels in olive oils may originate from varieties and altitude where olive trees are grown (Kiritsakis 1998). These findings are generally in accordance with French olive oils (Ollivier et al 2003), in which the values range from 0.74% to 1.14 %. There were chromatogram.…”
Section: Squalene Contentsupporting
confidence: 90%
See 2 more Smart Citations
“…The differences in squalene levels in olive oils may originate from varieties and altitude where olive trees are grown (Kiritsakis 1998). These findings are generally in accordance with French olive oils (Ollivier et al 2003), in which the values range from 0.74% to 1.14 %. There were chromatogram.…”
Section: Squalene Contentsupporting
confidence: 90%
“…The distribution of fatty acids in the oils of domestic cultivars was in agreement with those of authors working on Turkish olive oil varieties (Ersoy et al 2001;Dıraman and Hı7ıl 2004;Tous et al, 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009) and these values for foreign cultivars were similar to those reported for foreign olive oil varieties (Gutiérréz et al 1999;Gimeno et al 2002;Ollivier 2003;Poiana and Mincione 2004;Tous et al 2005). (Figure 2) based on their fatty acid profiles.…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
See 1 more Smart Citation
“…Some good starting points exist for the study of the application of multivariate statistics in the field of chemometrics [11], and in what concerns the particular case of discrimination and classification, important works with reviews and developments are also available [12]. Many recent examples of these concerns in relation to olive oils can be found in the literature, in the search for the best chemical or physical parameters or methodologies to use in authentication and assessment of quality or possible adulterations, recurring to a wide number of statistical techniques [13][14][15][16][17][18][19], and the need to couple several statistical techniques in order to attain good discrimination and reliable models for classification is now evident [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NIR technique was employed to detect fraudulent addition of other vegetable oils and olive pomace oil, to virgin olive oil (Wesley et al 1995;Yang & Irudayaraj 2001;Doweny et al 2002;Vlachos et al 2006); and for olive oil authentication (Bertran et al 2000;Downey et al 2003;Woodcock et al 2008). The chemical characterization of fatty acids and sterols (Ollivier et al 2006;Ollivier et al 2003;Aranda et al 2004;Leardi and Paganuzzi 1987), is useful for assessing quality and authenticity.…”
Section: Quantification Of Chemical Parameters In Olive Oilmentioning
confidence: 99%